STRATEGI PEMASARAN PRODUK TABUNGAN UMUM SYARI’AH DENGAN AKAD MUDHARABAH: BMT-UGT Nusantara - adib, roisul; Syarofi, Ahmad Muhtar; Azzahro , Amalia Rizka (Malang Prodi. Ahwal Al-Syakhsiyyah, IAI Al-Qolam, 2024)
The marketing strategy of sharia general savings products with a mudharabah contract at BMT-UGT Nusantara Capem Bantur uses the Mudharabah Agreement, namely the BMT plays the role of Mudharib and the members play the role of Shahibul Maal. The profits from the business are distributed according to the initial agreement between the two parties, which is 70%: 30%. This study uses qualitative methods obtained from primary and secondary data, with data collection through observation, documentation and interviews. Then the analysis technique used is to use a descriptive method, namely by providing a description of the subject being researched. The results of this study conclude that the first BMT-UGT Nusantara Capem Bantur has implemented 2 (two) types of marketing strategies, namely internal and external strategies. As for the internal: The internal strategy carried out is to determine employees who are originally domiciled in Bantur village even if they move from another village as long as they have settled in Bantur village, while externally: The external strategy carried out is to collaborate with partners, school institutions, community organizations (Muslimat), and sugarcane farmer groups. The two obstacles experienced when carrying out marketing activities carried out by BMT-UGT Nusantara Capem Bantur are the lack of public trust in financial institutions that have a background so dark that they experience trauma due to fraudulent investments, lack of public awareness of halal transactions, and people are used to using deposit services in conventional banks and the difficulty of finding genuine employees